Stress analysis of plate with opposite semicircular notches and adhesively bonded piezoelectric actuators - Abuzaid, Ahmed; Hrairi, Meftah; Kabrein, Hashim (JVE International, 2020)
Stress control of structures by means of active smart material has evolved in recent years. The structure's stress control can typically be considered as strengthening that effects the structure's load-carrying capability. The stress concentration cause by holes and notches produces a large variation and significant increase in stress. The control of the stress concentration and its distributions in the notched area is valuable for many practical and design applications. This study investigates the impacts of the piezoelectric actuators on control of the stress concentration factor (SCF) for an aluminum plate with opposite semicircular notches. Finite-element method (FEM) is used to access the SCFs due to external static loading. The stress control efficiency is assessed by the SCFs as an effectiveness criterion. The results indicate that SCFs reduces linearly with active piezoelectric actuator.